2020
DOI: 10.1111/jgh.15183
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota signatures and clinical manifestations in celiac disease children at onset: a pilot study

Abstract: Background and Aim Recent researches have shown an altered gut microbiota in celiac disease (CD) patients compared with healthy controls (HCs). This study aims to evaluate the composition of the microbiota of CD children at onset and the relationship between bacterial abundances and symptoms. Methods Celiac disease patients were consecutively enrolled at a pediatric unit referring for suspected CD. HCs were also included in the study. Stool and duodenal samples were collected and evaluated by a high taxonomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
51
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 49 publications
5
51
1
Order By: Relevance
“…Dysbiosis can promote celiac disease, and recent studies have established a link between dietary gluten (wheat, oats, barley, rye) and changes in the intestinal microbiome. Several studies suggest that modern lifestyle and eating habits may play a role in disrupting the balance of intestinal bacterial flora [ 53 ].…”
Section: Effectiveness In Promoting Health: Mechanism Of Action Ofmentioning
confidence: 99%
“…Dysbiosis can promote celiac disease, and recent studies have established a link between dietary gluten (wheat, oats, barley, rye) and changes in the intestinal microbiome. Several studies suggest that modern lifestyle and eating habits may play a role in disrupting the balance of intestinal bacterial flora [ 53 ].…”
Section: Effectiveness In Promoting Health: Mechanism Of Action Ofmentioning
confidence: 99%
“…The evidence of dysbiosis in CD patients [38][39][40] has gained more and more research on the use of probiotics for gut microbiota restoration and modulation. Indeed, the composition of gut microbiota influences the spectrum of gastrointestinal symptoms of this disease [40]; microbiological studies [26,41,42] showed a different abundance of Lactobacillus and Bifidobacterium strains in CD patients at disease diagnosis, other than a reduction in several 'health'-promoting bacterial strains, such as Akkermansia muciniphila, demonstrating an association with intestinal dysbiosis [43]. The unbalanced gut microbiota may indeed promote CD, influencing the mutualistic relationship between the colonic microbiota, their metabolic products, and the host immune system; in order to maintain immunological homeostasis, it is essential to establish a "healthy relationship" since the first years of life [44].…”
Section: Probioticsmentioning
confidence: 99%
“…After the screening by title, the duplicated records were removed, and 397 articles were assessed for eligibility based on the abstracts: of those, 114 full-text original articles were considered as eligible according to the aim of this systematic review. The final search output consisted of 18 articles describing the gut microbiota of CD children and including one or more control groups (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). All the articles finally included in this systematic review are listed in Table 2, where the study population, participants' age group, sample type(s), aim of the study, type of intervention, sample size, and detailed laboratory methods are summarized.…”
Section: Resultsmentioning
confidence: 99%